SUSTAINABLE DEVELOPMENT THROUGH RELIGIOUS ECOSOPHY: A Case Study of Tau Kaavu, Kochi, Kerala - M. P., Arya; Paul C., Betsy (Journal of Dharma, 2022)
This research paper explores religious ecosophy as one of the viable reparative means to the present global environmental crisis. The paper critiques Lynn White’s criticism of Western Christianity as bearing the moral burden of anthropocentrism, which led to the ecological emergency, and traces the ecologically-aligned history of Christianity, especially from the latter half of the twentieth century to the present. Guattari’s and Naess’ notion of “ecosophy,” Thomas Berry’s ideas on “eco-spirituality,” and Madhav Gadgil’s conception of the “sacred groves” are used to form the theoretical framework for the arguments put forth here. Locating the formative influences of Tau Kaavu in the inter-religious frameworks of Kerala, the paper projects it as an example of religious ecosophy and eco-spirituality that also caters to the Sustainable Development Goals 2030 envisioned by the United Nations in 2015. The significance and scope of the article lie in exploring the prospects of ecosophy in regards to global religions that can help produce ecologically allied ideologies and aid sustainable development.